The effect of e-commerce advertising exposure Lazada buying behavior teenagers at SMK Muhammadiyah 2 Surabaya - Susilo, Daniel; Chairiyah, Ummy (Universitas Dr.Soetomo, 2021)
The amount of interest of producers in using advertising as a medium for marketing products shows that advertising has an important role as an effective communication medium in introducing and promoting a product to consumers. Currently, advertisements have begun to mushroom in all mass media, including print media, electronic media and the internet. The high use of the internet in Indonesia has made producers more aggressive in promoting a product to consumers through internet media such as Lazada e-commerce ads. The number of facilities offered has received a very good response from the Indonesian people. With the ease of access provided and the relatively cheap prices of goods, it leads people to consumptive behavior.This study uses a quantitative approach. Survey research methods. This type of research explanatory research. The population in this study were students of SMK Muhammadiyah 2 Surabaya from the 2015-2017 class. The research sample was 186 people. This study has 2 independent variables (Ad Impression Intensity and Advertising Element), and 1 dependent variable (Buying Behavior). Data collection was carried out by distributing questionnaires.Hypothesis testing is done with multiple linear regression showing the influence between the intensity of advertising impressions and advertising elements on buying behavior, as evidenced by the results of the F test that Fcount> Ftable (111.280> 2.89). The result of the significance can be seen that 0.000 <0.05. The results of the T test for X1 show that the value of tcount <ttable (-1.494 <1.298), so the variable intensity of ad impressions has no effect on buying behavior. The results of the T test for X2 show that the value of tcount> ttable (14.521> 1.298), so the variable element of advertising has an effect on buying behavior.Â Keywords: Ad impression intensity; Advertising elements; Buying behavior